Marching ahead of time comprehensive development on China's road to national rejuvenation (China Intercontinental Press, 2017)
This book is a compilation of selected editorials and opinion articles published in China Daily over the past five years. The articles cover a wide variety of issues and reflect the views of domestic and foreign scholars and writers responding at the time to a new development. They not only highlight the challenges China has faced over the past five years and the many achievements it has made under the leadership of the Communist Party of China, but also explore how China will navigate its way to realize the people's dream of national rejuvenation. Collectively, the pieces examine the significance, influence and practical outcomes of new strategies, new thinking and new ideas introduced and implemented by the new leadership with General Secretary Xi Jinping as its core since late 2012. These have guided China's development in the era of a new normal and instigated 'deep-water' reforms in many areas that have given fresh impetus to social development, contemporary culture, the country's ecologic and environmental health, and China's growing contribution to global governance.